RESULTATS DU TRAITEMENT DU VOLVULUS DU SIGMOÏDE A N’DJAMENA, TCHAD - Choua Ouchemi; Kaboro Mignagnal; Ali Mahamat Moussa; Ahmat Malgnan Okim; Moussa Kalli M; Ndjianone Kalki N (European Scientific Journal, ESJ, 2015)
The sigmoid colon volvulus is a common cause of intestinal obstruction in Africa. This work aimed to describe the treatment of sigmoid volvulus in N'djamena, Chad. Materials and Methods: This was a retrospective descriptive study realized in the General Surgery Ward of the Hopital General de Référence Nationale of N'Djamena, Chad during the period from 1/1/2010 to 31/12/2014. The records of patients operated during that period were the source of the studied data collection. The study parameters were: age, gender, physical findings and functional signs, para clinical examinations, the presence or not of colonic necrosis, the type of treatment, length of hospital stay, morbidity and mortality. Results: Sixty six cases were retained. The sigmoid volvulus constituted 9% of the operated intestinal obstruction during the study period. They were 64 men (96.7%) and 2 women (3.03%) or a sex ratio of 32/1. The clinical signs were: abdominal pain (91.2%), abdominal distension ( 88.6), and a cessation of stools and gas. (73.6%) Moreover, vomiting was found in 58 % and fever in 29,% of cases. The mean time to diagnosis was 37.7 hours (range 6 hours and 101h). The necrosis rate was 16.6% or 11 cases. The operative techniques were: resection - colostomy according Hartmann in 33 cases (50%); resection followed by immediate colo-colonic anastomosis in 23 cases (34.85%), and a simple untwisting in 10 cases (15.15%). Morbidity was 13.6% represented by two anastomotic leaks in the group of resection anastomosis, 4 parietal wall suppurations, and two medical complications. The average hospital stay was 11.2 days (range 5 days and 58 days). Mortality was 5.4%, and all concerned three patients over 60 years and with comorbidities. Conclusion: In the management of sigmoid volvulus, the Hartmann procedure is the safest method in our context. Ideal colectomy may be propsed in selected cases. The simple untwisting of the colon by laparotomy is not recommended, because of frequent relapses.